Tobacco Smoke and Pregnancy Outcome: Literature Review - Haerani Harun1, Anwar Daud2, Veni Hadju3, Muh Syafar4, Ridwan Amiruddin5, Rahma6, Abdul Faris1 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Pregnant women have a risk for tobacco smoke both actively and passively. Various effects of tobaccosmoke on pregnancy have been investigated. Pregnant women are usually exposed to enviromental tobaccosmoke (ETS) in various places with different duration of time. Cigarette smoke has a severe effect not onlyon pregnant women but also on the fetus. This is a literature review. Various references were collected fromonline database including reports, journals, mostly in the last 10 years. The journals were mostly from thescholarly journals. The articles were screened according to the research objectives. The keywords usedare tobacco smoke, environmental tobacco smoke and pregnancy outcome. Tobacco smoke can effect theimmunity, hormonal and metabolic system of the pregnant woman, therefore disturbing the growth of thefetus. Tobacco smoke also known to increase the risk of premature birth and reduce gestational age. Tobaccosmoke cause several problems in newborn such as respiration distress, low birth weight (LBW), neuraldisorder, sudden infant death syndrome (SIDS) and congenital anomaly.The effect of tobacco smoke, actively of passively, have worse outcome for the pregnant women and theirbabies.